Molecular characterization of submergence tolerance genes and locus in the deep-water rice cultivars - Cuu, Nguyen Van; Khiem, Nguyen Van; Hoi, Pham Xuan (Vietnam Journal of Biotechnology, 2020)
Most of the rice cultivars exhibit suspension of growth when submerged to overcome the reduced availability of oxygen. When the situation continues, majority of the cultivars unable to recover after the flood recedes. However, there are fortunately some rice genotypes that can withstand such submerged condition for up to two weeks by adapting two totally opposite mechanisms. One type of cultivars elongates enormously at a very short span of time and the leaves come above the water level. In the second type, they remain under water without any growth. Cultivars of both types tolerate the submergence but the first category easily lodges when flood water recede. In those lines, yields are reduced drastically. In this study, we focus on characterize the genetic variation at the Sub1 locus and to associate its relevance, if any, to submergence tolerance among the deep water landraces. As a first step, seeds of some rice cultivars collected from North-east Indian regions were initially selected for the characterization of genetic variation. The PCR based analysis involving several genes known to be associated with submergence tolerance did not reveal much difference. However, Southern hybridization revealed certain differences between submergence tolerant and susceptible cultivars. Although we did not notice major difference with regard to Sub1 genes when tried with EcoRI and BamHI, differences were noticed with adh1 and RAmy3C genes. Representative, Southern analysis showed the genetic variation among the deep-water cultivars as compared to Swarna and Sub1-Swarna. It is possible that deep-water rice cultivars may not differ in their genome at Sub1 locus but they respond through SNORKEL genes under submergence.